Interculturality as a Competence in Higher Education: Validation of an Instrument with University Students - De Santos Velasco, Francisco Javier (2018)
This article, based on the results of a doctoral thesis study, deals with two aspects: the adaptation and validation of an instrument to measure the intercultural sensitivity of university students and the relationship between the measurement of the intercultural sensitivity scale versus the experience profile of university students in the face of international and/or the multicultural experiences. The instrument was applied to 280 students from Universidad Pompeu Fabra in Barcelona, Spain. The results of the analysis of the technical characteristics of the scale indicate that it has content validity and that the instrument scores are reliable. It was found that all variables related to direct international and/or multicultural experience appear with a significant difference, except for the variable referring to number of foreign teachers, which supports research works that have found that the learning of the intercultural competence is an active process of constant learning throughout life, with a high experiential component, i.e., that it is carried out mainly through direct experience with “the other different,” either in one-to-one or group interactions, either in their own country or abroad.